The Analysis Of Code Mixing In Maudy Ayundaâ€™s Vlog â€œStress Managementâ€ - Nita Dianah; Hanif Nurcholish Adiantika; Susilawati Susilawati (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2025)
Nowadays, many people use code-mixing in their daily lives. Therefore, content creators use it as a tool to introduce culture and provide information to audiences who may not be familiar with the language. This research decided to find the types of code-mixing in Maudy Ayunda's "Stress Management" vlog. The method used to conduct this research is descriptive qualitative method. The subject of this research is Maudy Ayundaâ€™s utterances. This research used spoken discourse to collect the data. For collecting the data the spoken utterances in Maudy Ayunda â€œStress Managementâ€ vlog were watched, read and listened. In collecting the data of code mixing was found that Hybrid Insertion is inserting foreign language elements in the mother tongue. Hybrid Insertion is found 7 times, while Word Insertion is 6 times, Phrase Insertion 2 times, Repetition Insertion 5 times, Indiom Insertion 0 times and Clause Insertion 1 time. It is concluded that Maudy most often uses Hybrid Insertion rather than other types.